A NEW MACULAR DYSTROPHY SECONDARY TO A NOVEL MUTATION IN THE PROMININ 1 (PROM1) GENE. (2017) - Randhawa, Sandeep; Sharma, Mithlesh
Abstract : Purpose: To report a case of a new macular dystrophy caused by a novel mutation in the PROM1 gene. Methods: History and clinical examination, fluorescein angiography, optical coherence tomography, autofluorescence, electrophysiology, and genetics. Results: We report a case of a 51-year-old man with progressive central visual loss in both his eyes. On fundus examination and imaging, there were asymmetric atrophic macular lesions in both his eyes. Electrophysiology revealed a bilateral macular atrophy; genetic testing revealed a novel PROM1 mutation as the probable cause. Conclusion: A novel PROM1 mutation as the cause of a new bilateral macular atrophy is revealed. Abstract : This case describes a new macular dystrophy due to a novel mutation in the PROM1 gene.